PENGARUH KARAKTERISTIK KEUANGAN PERUSAHAAN, STRUKTURAL KEPEMILIKAN, DAN DAMPAK COVID-19 TERHADAP KINERJA PERUSAHAAN DAN NILAI PERUSAHAAN - Febriyanti, Amaria; Triyono, Triyono (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the influence, financial characteristics, structural ownership and covid-19 on company value with company performance as an intervening variable in food and baverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study is manufacturing companies engaged in the food and beverage sector. Sampling is done using purposive sampling. This research method uses multiple linear regression. Sobel test in this study was used to analyze indirect influence on work performance as an intervening variable. The results of the study concluded that liquidity, solvency, capital expenditure, and managerial ownership affect company performance, while Covid-19 and institutional ownership do not affect company performance. Company performance affects company value, while Covid-19, liquidity, solvency, capital expenditure, managerial ownership and institutional ownership have no effect on company value. The company's performance cannot mediate covid-19, liquidity, solvency, capital expenditure, managerial ownership and institutional ownership of the company's value in the food and baverage sub-sector companies